The science of james bond : - Gresh, Lois H. (J. Wiley & Sons, 2006)
The Science of James Bond takes you on a fascinating excursion through the true science that underlies Bond's most fantastic and off-the-wall accoutrements. The acclaimed science-fiction authors Lois Gresh and Robert Weinberg provide a highly entertaining, informative look at the real-world achievements and brilliant imaginations behind such singular Bond gadgets as the buzz-saw Rolex, the car that turns into a submarine, and the ever-popular rocket-firing cigarette. They examine hundreds of Q Division's ingenious inventions; analyze Bond's astonishing battles beneath the earth and sea, in the skies, and even in outer space; and ask intriguing questions that lead to enlightening discussions about the limits of science, the laws of nature, and the future of technology.